Ureteral Stent Induced Urinary Tract Infection and Microbial Inconsistency Between Bladder and Renal Pelvis - Useok Choi; Eun Jae Kim; Don Hee Lyu; Bong Hee Park; Hong Chung; Chang Hee Han; Sangrak Bae (Urogenital Tract Infection)
Purpose This study examined the effects of long-term ureteral stent (US) on urinary tract infection (UTI) by bacterial migration and bacterial colonization. Materials and Methods From March 2014 to August 2021, 64 patients who underwent US for more than six months were enrolled in this study. When the US was inserted for the first time and replaced regularly, urine was collected from the bladder and renal pelvis and cultured. Patients’ the characteristics, and differences in pathogens related to US infection were analyzed. Results The mean age was 66.4 years, and the mean duration of indwelling was 37.5 months. There were 38 cases (59.3%) by malignant and 26 cases (40.6%) by benign causes. UTI occurred in 33 cases (53%); 16 cases (25%) were hospitalized for febrile UTI. After the initial US insertion, bacteria were identified in the bladder 285 days later and in the renal pelvis after 619 days. The bladder culture was positive in 10 of the 33 patients, and renal pelvis alone was positive in nine of the 33 patients. The same strain was confirmed in the bladder and renal pelvis in 12 cases (18.8%), and it took a mean of 5.8 months ± 6.32 (standard deviation) for the upward migration of bacteria. Conclusions UTIs occur in approximately 50% of patients with long-term US indwelling. The probability of culturing the same strain by a US was approximately 18.8%, and the role of pathogen transmission of a US does not appear to be significant. In addition, renal pelvis culture would be helpful in cases of failed bladder antibiotics susceptibility.